Gender Differences in Throwing Revisited: Sensorimotor Coordination in a Virtual Ball Aiming Task - Crozier, Dena; Zhang, Zhaoran; Park, Se-Woong; Sternad, Dagmar (Frontiers in Human Neuroscience, 2019)
Numerous studies have demonstrated that boys throw balls faster, farther and more accurately than girls. This may be largely due to well-known anatomical and muscle-physiological differences that play a central role in overarm throwing. With the objective to understand the potential contribution of the equally essential coordinative aspects in throwing for this gender difference, this large cross-sectional study examined a simplified forearm throw that eliminated the requirements that give males an advantage.While the overall performance error indeed became similar in the age groups younger than 20 years and older than 50 years, it was attenuated for middle-aged individuals. The gender differences remained in individuals who reported no throwing experience, but females with throwing experience reached similar performance as males. Two fine-grained spatiotemporal metrics displayed similar age-dependent gender disparities: while overall, males showed better spatiotemporal coordination of the ball release, age group comparisons specified that it was particularly middle-aged females that made more timing errors and did not develop a noise-tolerant strategy as males did. As throwing experience did not explain this age-dependency, the results are discussed in the context of spatial abilities and video game experience, both more pronounced in males. In contrast, a measure of rhythmicity developed over successive throws only revealed weak gender differences, speaking to the fundamental tendency in humans to fall into rhythmic patterns. Only the youngest individuals between 5 and 9 years of age showed significantly less rhythmicity in their performance. This computational study was performed in a large cohort in the context of an outreach activity, demonstrating that robust quantitative measures can also be obtained in less controlled environments. The findings also alert that motor neuroscience may need to pay more attention to gender differences.